(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The purpose of the study was to appraise the management practices of National Examinations Council (NECO) on personnel, infrastructural and financial management of Council fund. Three research questions and three null hypotheses guided the study. The population were 154NECO Senior administrative staff and 44Heads of Departmentmaking a total of 198 respondents. There was no sampling carried out because the population was small so the entire population was used. The design of the study was a descriptive survey. The research instrument was a questionnaire titled “Appraisal of Management practices questionnaire (AMPQ) and was validated by experts. The instrument was assessed for reliability using internal consistency of Cronback Alpha method. The reliability coefficient obtained yielded 0.92. The data obtained were organized and analyzed using the mean and standard deviation to answer research questions and t-test to test the null hypotheses. Some of the major finding revealed that NECO management adhered to the regulation system (manual) in the personnel, infrastructural, and financial management of the Council. The hypotheses tested indicated no significant difference in the mean rating of both NECO senior administrative staff and heads of Department on the extent to which NECO management adhered to the regulation system (manual) on personnel, infrastructural and financial management ofthe Council. Based on the findings, the researcher recommended that NECO management should continue to be guided by NECO rules and regulation in personnel, infrastructural and financial management of the Councilamong others.